Students’ Strategies In Revising Writing Draft After Receiving Teacher Feedback - Dwipantoro, Diknas Adi; Mafulah, Siti (Universitas Muhammadiyah Gresik, 2024)
The aim of this study was finding out students' strategies in revising draft after receiving feedback in Essay Writing class. Qualitative method was applied in this study with the different intake participants at one of University in Malang, Indonesia. The research instruments were questionnaires, the questionnaire was delivered to 27 students and from the result of questionnaire was chosen randomly 9 students to be interviewed. In analyzing the data, data reduction, data display, and conclusion drawing/verification were done. To validate the data, data triangulation techniques was applied. The finding shows that most students received direct feedback from the lecturer in Essay Writing class. In carrying out revisions, students have strategies for revising their draft. Students did revision strategies through translating from online dictionary, reviewing of errors before the exam, consultating with lecturer, sharing with friends, translating from bilingual dictionary, and recording the lecturer voice. Besides, students carried out revision operation including Deleting, Reorganization, Addition, Correcting, Rewriting, Substituting, and No Correcting. From the result of this study, it can be concluded that students have different ways in revising their writing based on their preference and need. Therefore, teacher should treat the students in different ways in giving feedback.